(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Water is one of the world’s most important natural resources without which humans cannot survive and rain is a major source of it. Water is the key to health. It is one of our basic needs for survival. Alwar had many water sources but in recent years, it has experienced significant reductions in water levels reaching even in the dark. Rainfall is one of the main causes. Over the past decade, the average rainfall of the alwar has dropped dramatically, to 64cm in 2010-2011. Such declines cause rapid groundwater depletion in alwar. Previously, groundwater runoff was around 0.30 m per year but has now reached about 1m per year. The worst affected areas are the Behror and Neemrana block where the water level reached a depth of more than 40 meters. The main cause of last year’s rainfall is seasonal changes due to global warming. Now is the time to take the matter seriously. Overall, we can reverse the decline in water levels by harvesting rainwater and other management measures, so that levels can improve slightly. The Alwar region in Rajasthan is considered to be the dry part of the country. The only source of renewable water supply to the region is rainfall as many rivers have certain seasons. Therefore, the region needs a major water harvest to rehabilitate groundwater in a traditional and modern way. That is why ’johad’ plays an important role in this region.